2002
DOI: 10.1525/tsq.2002.43.4.607
|View full text |Cite
|
Sign up to set email alerts
|

When the Screen Goes Blank: A Television Plant Closing and Its Impacts on Workers

Abstract: Using survey and interview information, the impacts of job loss 011 former employees of a Zenith Corporation plant in Springfield, Missouri, are identified and placed in the context of existing research findings. Even in the "New Economy" period of national economic expansion and in a robust local job market, many displaced workers endured significant drops in earnings and benefits and experienced decreased work satisfaction. Although women took longer than men to become reemployed, displacement did not lead m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Interestingly, as Doucet (2004) showed, men also account for job loss, which they and others construe as a sort of gender deviance. For example, Knapp and Harms (2002) showed that men were more likely to have reservations about rejoining the workforce due to availability of family income. Similarly, men who lost work were more likely to blame the government-not themselves (Perrucci, Perrucci, Targ, & Targ, 1988).…”
Section: Bread-losing: Structural Disruption Through Economic Crisismentioning
confidence: 99%
“…Interestingly, as Doucet (2004) showed, men also account for job loss, which they and others construe as a sort of gender deviance. For example, Knapp and Harms (2002) showed that men were more likely to have reservations about rejoining the workforce due to availability of family income. Similarly, men who lost work were more likely to blame the government-not themselves (Perrucci, Perrucci, Targ, & Targ, 1988).…”
Section: Bread-losing: Structural Disruption Through Economic Crisismentioning
confidence: 99%
“…Women who have more concerns about the stability of their jobs are more likely to state the intention to reenroll in college (Smart & Pascarella, 1987). Regardless of the extent to which education leads to a comparably salaried job, most evidence indicates that many displaced workers choose education following lay-offs (Ghilani, 2008;Knapp & Harms, 2002).…”
Section: Displaced Worker Statusmentioning
confidence: 99%
“…Although there are veins of research which address the consequences of economic shocks for communities, they tend to focus primarily on large disruptions involving one type of shock, focus on a limited sample size, and are conducted only after the shock has occurred. Examples include studies that examined boomtowns (Brown, Dorius, and Krannich, 2005;Smith, Krannich, and Hunter, 2001;Greider, Krannich and Berry, 1991), factory closings (Broadway and Stull, 2006;Uchitelle, 2006;Broadway and Stull, 2006;Knapp and Harms, 2002), and natural disasters (Erickson, 1994;Drabeck, 1986;Erikson, 1976). In contrast, I utilize a relatively large sample of communities and examine the consequences of several economic shock types and the cumulative effect of multiple economic shocks across 99 small Iowa communities.…”
Section: The Significance Of This Researchmentioning
confidence: 99%
“…Towns that were generally not lifted by the rural rebound were located in the Corn Belt, Mississippi Delta, and Great Plains (including Iowa). On average, these towns saw declines in both population and employment opportunities (Whitener, 2005;Johnson 2003 (Broadway and Stull, 2006;Uchitelle, 2006;Knapp and Harms, 2002;Illes,1996;Dudley, 1994;Perucci, 1988;Bluestone and Harrison, 1982). As a consequence of declining employment opportunities and a lack of desirable natural resource amenities, many of the rural communities in the heartland lost their "best and brightest," the young, most highly educated, and most skilled of its population (Lichter, 1995: 254).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation